Introducing StreetSnap: An Initiative to Transform the Capture, Recording & Intelligence Gathered about Hate Graffiti across the Bridgend County Borough - Lella Nouri (2023)
The development of a monitoring instrument to streamline processes is fundamental and has been made possible through Welsh Government SMART Partnership Funding. This funding has enabled a multi sector approach, joining Swansea University academics and technological expertise from Legal Innovation Lab Wales with Bridgend County Borough Council. This report delineates the case for this academic, evidence unique technological solution which can simultaneously support staff and address multiple Policy agendas, achieving participatory and transformational change, having societal, economic, and technological impact.based, unique technological solution which can simultaneously support staff and address multiple Policy agendas, achieving participatory and transformational change, having societal, economic,and technological impact.